2016
DOI: 10.1002/bdra.23552
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of the glycine cleavage system genes and myelomeningocele

Abstract: Background Neural tube defects (NTDs) are one of the most common congenital birth defects, with myelomeningocele (MM) being the most severe form compatible with life. Recent studies show a link between mitochondrial folate one carbon metabolism and NTDs via the glycine cleavage system (GCS). We hypothesize that single nucleotide polymorphisms (SNPs) and novel variants in the coding regions of the GCS genes increase the risk for MM. Methods DNA was obtained from 96 subjects with MM born before the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…7 More recently, several candidate variants were identified in AMT and GLDC, 2 of the genes constituting the mitochondrial GCS. 10,32 In the present study, we identified a novel missense variant affecting the catalytic domain of the MTHFR gene. This patient additionally carried the c.677C>T variant, and a rare missense variant (c.2203G>T) in the GLDC gene.…”
Section: Folate One-carbon Metabolismmentioning
confidence: 75%
See 1 more Smart Citation
“…7 More recently, several candidate variants were identified in AMT and GLDC, 2 of the genes constituting the mitochondrial GCS. 10,32 In the present study, we identified a novel missense variant affecting the catalytic domain of the MTHFR gene. This patient additionally carried the c.677C>T variant, and a rare missense variant (c.2203G>T) in the GLDC gene.…”
Section: Folate One-carbon Metabolismmentioning
confidence: 75%
“…30 GLDC encodes a component of the glycine cleavage system (GCS) in mitochondrial folate one-carbon metabolism, which has previously been implicated in both mouse and human NTDs. 10,11,31,32 Another individual with anencephaly (706F07) was heterozygous for a missense variant (c.200C>T; p.…”
Section: Relatedness Analysismentioning
confidence: 99%
“…Threonine is an essential amino acid that is used in the body for tissue protein synthesis, mucin production by the enterocytes of the intestine, and as a precursor for glycine (Shah, Northrup, Hixson, Morrison, & Au, ). Glycine was recently shown to be involved in the etiology of neural tube defects (Ouyang, Li, Liu, Chang, & Wu, ).…”
Section: Discussionmentioning
confidence: 99%
“…57,58 Furthermore, variants in AMT and GLDC that may contribute to human NTD risk have been identified in several studies. [56][57][58][59] After folates are transported to mitochondria, they are oxidized to formate by the actions of mitochondrial enzymes MTHFD2/2L…”
Section: Interrogation Of High Probability Networkmentioning
confidence: 99%